Pengaruh Penggunaan Medial Arch Support Terhadap Penurunan Derajat Flat Foot Pada Anak Usia 8 – 12 Tahun - Prasetyo Catur Utomo; Dwi Setyawan; Muhammad Fathi (Jurnal Keterapian Fisik, 2018)
Abstract Background: The World Health Organization (WHO) provides evidence that there are hundreds of millions of people affected by life due to musculoskeletal disorders. Musculoskeletal disorders that are often found are flat foot or commonly called flat foot. In the treatment of flat foot, prosthetic orthotics can provide orthosis services in the form of medial arch support with sponge and plastic material, which aims to provide support to the plantaris area of the foot and restore the shape of the arch to the foot. Method: This type of research is Quasi Experiment with two groups design Pre Test and Post Test Design. The population in this study included students of grades 2-6 at SDN Gagaksipat 1, Ngemplak, Boyolali, Central Java. The number of samples is 28 students. Data collection techniques using the wetfootprint pre test and post test. Results : There is an effect of using medial arch support on the reduction of flatfoot degrees. These results can be seen from the results of Wilcoxon test, which is known below the p value = 0,000. Then if the value of p <0.05. Conclusion: It can be concluded that there is an effect of medial use arh support for decreasing flatfoot degrees in children aged 8-12 years. From the results of the study it was found that there were 28 research samples that experienced a decrease in the degree of flatfoot.